Pengolahan air limbah industri penyamakan kulit menggunakan abu terbang bagas secara batch - Sholeh, Muhammad; Prasetya, Agus; Sarto, Sarto (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 2012)
The objective of this research was to evaluate the adsorption ability of chemically activatedÂ bagasse fly ash using H O or H SO to remove COD from tannery wastewater and to obtain 2 adsorption isotherm model in batch system. Two stages have been carried out, namely the activation experiment and the adsorption isotherm experiment. In the activation experiment, effect of H O dan H SO (3% and 7,5% w/w) were studied. The best result of the variation was used in the next experiment. In the adsorption isotherm experiment, variation of the initial concentrations of COD from 52,53 to 1665,79 mg/L and mass of bagasse fly ash from 0,1 to 0,4 g were used. Equilibrium data was used to evaluate the parameters in the Langmuir, Freundlich, and Temkin equations. The best model was evaluated using determination coefficients. The results showed that bagas fly ash had better ability to reduce the COD when it was not activated with H O nor H SO (3% and 7,5%). Freundlich model was best to describe COD removal using bagasse fly ash in batch system. Freundlich equation constants K and n were F 0,4360 (mg/g)/(L/mg)1/n and 1,2969 respectively and the determination coefficient obtained was 0,93.Â Â Keywords: Chemical Oxygen Demand, tannery wastewater, bagasse fly ash, adsorption